Study of Mercury and Arsenic Contamination in Gold Processing Tailings from Gunung Botak, Buru Island – Maluku - Siahaya, Anto Netty; Tanasale, Matheis Frits Jan David Pieter; Joris, Shielda Natalia; Hasimin, Muhammad Syahyono; Choesni, Filky Sky (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2026)
Buru Island in Maluku Province is one of the sites of unlicensed gold mining activities (Illegal Gold Mining, IGM), which may lead to environmental pollution due to improper waste management. This study aimed to analyze the concentrations of mercury (Hg) and arsenic (As) as hazardous pollutants (Hazardous and Toxic Materials, HTM) in gold processing tailings from Dafa and Debowae Villages, Buru Island. Tailings samples were collected from three different sites. Mercury concentrations were determined using Cold Vapor AAS, while As was analyzed using Hydride-Generation AAS based on the APHA-AWWA-WEF standard method (2005). The results showed that Hg levels in tailings from Debowae Village (Location 1 and 2) were 399.18 mg/kg and 286.39 mg/kg dry weight, respectively, whereas Dafa Village (Location 3) reached 1182.51 mg/kg dry weight. Arsenic concentrations ranged from 0.59 to 0.74 mg/kg dry weight across all locations. According to Indonesia Government Regulation PP No. 22 of 2021 on Hazardous Waste Management, Hg concentrations in all study sites exceeded the quality standard, whereas As levels remained below the permissible limits. These findings highlight the serious potential risk of mercury contamination in artisanal gold mining areas on Buru Island.